Konsep Dasar Pendidikan Anak Usia Dini Dalam Perspektif Islam (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The aim of this research is to find out and analyze the basic concepts of Early Childhood Education. The research method used is descriptive qualitative. The results of this research state that early childhood education is a form of education that focuses on laying the foundation for growth and development of physical, intelligence, socio-emotional, language, communication, in accordance with the stages of development that early childhood goes through. Early childhood education is very important because early childhood will determine the character of students throughout their educational journey correctly and appropriately. Childhood education really determines overall success in the future, including the implementation of learning in preschool which will help children face the real world. In childhood, this is the initial foundation for educating children.